Neratinib protects pancreatic beta cells in diabetes - Amin Ardestani (Nature Portfolio, 2019)
Type 1 as well as type 2 diabetes are characterized by a loss of insulin-producing β-cells. Here the authors show that the FDA-approved drug neratinib has beneficial effects on β-cell survival, insulin secretion, and glycemic control in mouse models of diabetes.